2000
DOI: 10.1128/iai.68.12.7087-7093.2000
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Nuclear Factor κB and Induction of Inducible Nitric Oxide Synthase byUreaplasma urealyticumin Macrophages

Abstract: Chronic lung disease (CLD) of prematurity is an inflammatory disease with a multifactorial etiology. The importance of Ureaplasma urealyticum in the development of CLD is debated, and steroids produce some improvement in neonates with this disease. In the present study, the capability of U. urealyticum to stimulate rat alveolar macrophages to produce nitric oxide (NO), express inducible nitric oxide synthase (iNOS), and activate nuclear factor B (NF-B) in vitro was characterized. The effect of NO on the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Nitric oxide is a soluble, shortacting free-radical gas produced by a variety of cells that mediates a number of functions involved in the local inflammatory response. Two studies have demonstrated the ability of Ureaplasma to stimulate rodent macrophage cell lines to release nitric oxide (59,169). Nitric oxide production induced by Ureaplasma can be down-regulated by administration of corticosteroids (169).…”
Section: Association Of Ureaplasma Spp With Development Of Chronic Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide is a soluble, shortacting free-radical gas produced by a variety of cells that mediates a number of functions involved in the local inflammatory response. Two studies have demonstrated the ability of Ureaplasma to stimulate rodent macrophage cell lines to release nitric oxide (59,169). Nitric oxide production induced by Ureaplasma can be down-regulated by administration of corticosteroids (169).…”
Section: Association Of Ureaplasma Spp With Development Of Chronic Lmentioning
confidence: 99%
“…Several recent investigations have examined the relationship between ureaplasmal colonization of the neonatal respiratory tract and release of inflammatory mediators that may be involved in pathogenesis of BPD, including clinical studies (154,214,309) evaluation of cell lines from humans or rodents cultivated in vitro and exposed to Ureaplasma antigen (59,(166)(167)(168)(169)187), and animal models (308,338). Ureaplasma spp.…”
Section: Association Of Ureaplasma Spp With Development Of Chronic Lmentioning
confidence: 99%
“…We focused on pulmonary inflammatory cells and related NF-B activation to TNF-␣ and IL-8 levels in tracheal aspirates from these infants. Perinatal factors that may contribute to lung inflammation include chorioamnionitis (21,22) and Ureaplasma urealyticum colonization/infection of the airway (23)(24)(25)(26)(27). We determined whether these conditions are also associated with evidence of NF-B activation in the infant lung.…”
mentioning
confidence: 99%
“…Because TNF-␣ plays a major role as a stimulator of chemokines in the lungs of premature neonates, we speculate that the early treatment with AZM may provide antiinflammatory protection by suppressing the activation of NF-B and reducing the synthesis of NF-B-dependant proinflammatory mediators. Infection and colonization of the respiratory tract with ureaplasma and Mycoplasma may also trigger a vigorous pro-inflammatory response in the lungs and increase the risk for the development of BPD in preterm infants (32). Ureaplasma urealyticum increases the activation of NF-B in alveolar macrophages (33).…”
mentioning
confidence: 99%